Spectroscopic, Raman, EMPA, Micro-XRF and Micro-XANES Analyses of Sulphur Concentration and Oxidation State of Natural Apatite Crystals - Bo Xu; Guanyu Kou; Barbara Etschmann; Daiyue Liu; Joël Brugger (Crystals, 2020)
Sulphur is the third most abundant volatile element in deep Earth systems. Analytical methods for accurately and efficiently determining the sulphur content and oxidation state in natural minerals are still lacking. Natural apatite is widely distributed in the Earth and incorporates a large amount of sulphur. Therefore, apatite is an ideal mineral for performing sulphur measurements. Here, we used spectroscopic, Raman, X-ray diffraction, laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), electron microprobe (EMPA) and micro-X-ray fluorescence spectrometry (micro-XRF) analysis techniques and developed a new analytical approach (i.e., micro-X-ray absorption near-edge structure (micro-XANES) analysis of the sulphur K-edge) to investigate the chemical characteristics of natural apatite. These multiple methods were developed to measure in situ sulphur concentration and S oxidation states and to assess a potential natural apatite reference material. Apatite contains chemically homogeneous sulphur, with micro-XANES located at the peak energies corresponding to S6+ (sulphate; ~2482 eV), S4+ (sulfite; ~2478 eV), and S2− (sulphide; ~2467, 2470 and 2474 eV). The Durango apatite contains total S presented as SO3 at amount of 0.332 ± 0.012 wt.% (1σ), with a large amount of S6+ and a small contribution of S4+. The Kovdor apatite contains 44–100 ppm of S and is dominated by S6+. These results indicate that the Durango apatite crystallised under relative oxidising conditions, and the Kovdor apatite has a higher oxygen fugacity than Durango. In addition, this study indicates the potential use of the natural apatite reference material with its S composition and S oxidation state.